Application of the AHP-ELECTRE Method for Selection OOP Based Apps Programs - Akmaludin, Akmaludin; Suriyanto, Adhi Dharma; Iriadi, Nandang; Santoso, Budi; Wahid, Bilal Abdul (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Object-based programming (OOP) has become a trend among programming language users, this is because many functions, procedures and techniques for using features are so widely available. By utilizing the advantages of these facilities, it is possible to provide convenience for programmers who use object-based programming languages. The purpose of this study is to provide an objective scoring system for a number of programming applications that have been made equipped with the assessment criteria. Assessment criteria that can be used for object-based apps programs with eleven criteria, namely Class structure, Inheritance, Encapsulation, Pollymorphys, Constructur, Accessor, Mutator, Visibility, Overriding, Overloading, and Price. With these many criteria, it provides a level of difficulty in choosing an object-based program application. To determine the appropriateness of an apps program, source testing will be carried out in the form of coding that has been previously constructed which affects the eleven predetermined measurement criteria. The assessment process recommends using the Electre method as a measure of the results of the calculation and ranking process. While determining the weight of the criteria using the Analytic Hierarchy Process (AHP) method. From the results of the assessment of 23 object-based apps programs, ranking assessments are based on aggregate dominant matrices as follows, the first rank with a weight of 22 as the largest weight is owned by 4 apps programss, namely AP16, AP17, AP18, and AP19. Based on the results of the ranking process, it can be said that the ELECTRE and AHP methods can be used as a selection process for object-based apps programs with optimal results.